2017
DOI: 10.22159/ajpcr.2017.v10i4.16716
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Hand Hygiene Practices among Healthcare workers in Neonatal and Paediatric Intensive Care Unit of a tertiary care hospital of Odisha

Abstract: Objective: The objective of this study was to assess the knowledge of hand hygiene of health-care workers in the neonatal and pediatric intensive care unit in a tertiary care hospital. Methods:A study was conducted to assess the knowledge of hand hygiene for the five moments of hand hygiene of the World Health Organization. Health-care workers were given a questionnaire during routine patient care on a random basis and the data were collected. Data analysis was performed using SPSS software version 13.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Another combination of Chinese and western medicines included Lopinavir/Ritonavir, arbidol and Shufeng Jiedu significantly improved the pneumonia symptoms in China [95].  Self-monitoring the signs and symptoms of COVID 19 and report the illness to managers  Ensure that workplace and all the surfaces exposed to patients are cleaned and disinfected properly  Search for the travel history of all the National and International travellers in past few months who came to them with respiratory symptoms  If the patient is suspected with the disease in OPD they should be provided with masks immediately  Examiners should use surgical masks and practice hand hygiene frequently  Suspected cases should be isolated immediately and informed to diagnostic centres of respective state [96][97][98]…”
Section: Ivigmentioning
confidence: 99%
“…Another combination of Chinese and western medicines included Lopinavir/Ritonavir, arbidol and Shufeng Jiedu significantly improved the pneumonia symptoms in China [95].  Self-monitoring the signs and symptoms of COVID 19 and report the illness to managers  Ensure that workplace and all the surfaces exposed to patients are cleaned and disinfected properly  Search for the travel history of all the National and International travellers in past few months who came to them with respiratory symptoms  If the patient is suspected with the disease in OPD they should be provided with masks immediately  Examiners should use surgical masks and practice hand hygiene frequently  Suspected cases should be isolated immediately and informed to diagnostic centres of respective state [96][97][98]…”
Section: Ivigmentioning
confidence: 99%
“…Improper hand wash does not lead to complete eradication of germs and can be a reason for infection. Factors involved lack of education, poor hygiene habit, perceived lack of importance, lack of time, dry skin, skin irritation or dermatitis, the absence of suitable cleansing agent and inadequate hand washing 18,19 . Spread of antibiotic-resistant strains MRSA through the hands were reported by researchers 20 .…”
Section: Fig 3: Represents Five Steps At Which Hand In Health Care [mentioning
confidence: 99%
“…General practices including hand wash before and after patient care, avoid touching inanimate object, wearing of gloves and mask while cleaning contaminated goods and learning than about sterilization of equipment used in patient care 19 .…”
Section: Fig 5: Represents Air Pressure Control In Infectious Isolatmentioning
confidence: 99%
“…Previous studies on knowledge of HH among health workers reported varying results ranging from 15.5% to 99.3%. [ 8 9 10 11 12 13 14 15 ] However, little is known about knowledge of HH among eye care workers.…”
Section: Introductionmentioning
confidence: 99%